Roland Barthes writing the political history, dialectics, self - Stafford, Andy 1965- (Anthem Press, 2023)
A re-reading and a re-purposing for the twenty-first century of the critical theories of France's most important writer of the twentieth century. The volume argues that Barthes's wide-ranging analyses - from Voltaire to Nietzsche, Marx to myth, gay love to Japan - can be applied to debates and controversies in the contemporary world